The expression of ‘interest’ in the amicus curiae presented by the civil society before the International Criminal Court - Montero Ferrer, Carmen (2020)
In the current stage of Public International Law, access of the individual and organized civil society to international courts, just like participation in proceedings is a constant. In particular, through the institution of the amicus curiae, traditionally defined as the ‘neutral bystander’ who voluntarily intervenes in a dispute, assisting the court in the resolution of the case. This definition has evolved at the international level, so that in some cases the intervention of amici has been allowed to have an interest in the outcome of the procedures. However, the expression of interest is not expressly regarded as a criterion for determining the admission or rejection of amicus curiae in the rules of international criminal courts. In this sense, the Rome Statute of the International Criminal Court is no exception. For this reason, the present paper carries out a normative and jurisprudential analysis of the legal effects arising from the expression of interest in the pleadings submitted by civil society to the International Criminal Court.